Institutional framework for development of north-east India: The role of the North-Eastern Council - Ramabrahmam, Ivaturi; Hnamte, Lalnundika (2016)
The North-Eastern Region (NER), in the decades following the independence of India, was faced with administrative challenges including socio-economic backwardness, huge infrastructural gap with mainland India, regionalism and insurgent movements for independence. With the emergence of new political units as a result of the reorganisation of the region, the North-Eastern Council (NEC) was created by an Act of Parliament in 1971 to act as an intergovernmental organ and to coordinate the constituent units towards a planned development. This article also analyses how this institution can be made more efficient and vibrant. - Reproduced.
Keywords: Economic and social development - India, North East; Economic and social development